Bringing the biosphere home : learning to perceive global environmental change - Thomashow, Mitchell (MIT Press, 2002)
A guide for understanding the ecological and existential aspects of global environmental change. This book shows how to make global environmental problems more tangible, so that they become an integral part of everyday awareness. At its core is a simple assumption: that the best way to learn to perceive the biosphere is to pay close attention to our immediate surroundings. Through local natural history observations, imagination and memory, and spiritual contemplation, we develop a place-based environmental view that can be expanded to encompass the biosphere. Interweaving global change science, personal narrative, and commentary on a wide range of scientific and literary works, the book explores both the ecological and existential aspects of urgent issues such as the loss of biodiversity and global climate change. Written in a warm, engaging style, Bringing the Biosphere Home considers the perceptual connections between the local and global, how the ecological news of the community is of interest to the world, and how the global movement of people, species, and weather systems affects the local community. It shows how global environmental change can become the province of numerous educational initiatives--from the classroom to the Internet, from community forums to international conferences, from the backyard to the biosphere. It explains important scientific concepts in clear, nontechnical language and provides dozens of ideas for learning how to practice biospheric perception.